Ostial dimensional changes after pulmonary vein isolation: Pulsed field ablation vs radiofrequency ablation - Kuroki, Kenji; Whang, William; Eggert, Charles; Lam, Jeff; Leavitt, Jonas; Kawamura, Iwanari; Reddy, Ananya; Morrow, Blake; Schneider, Christopher; Petru, Jan; Turagam, Mohit K; Koruth, Jacob S; et al. (Heart rhythm, 2020)
BACKGROUND: Pulmonary vein (PV) stenosis is an important potential complication of PV isolation using thermal modalities such as radiofrequency ablation (RFA). Pulsed field ablation (PFA) is an alternative energy that causes nonthermal myocardial cell death. OBJECTIVE: The purpose of this study was to compare the effect of PFA vs RFA on the incidence and severity of PV narrowing or stenosis. METHODS: Data were analyzed from 4 paroxysmal atrial fibrillation ablation trials using either PFA or RFA; because of absent CT scans or poor computed tomography scan quality, 73 of 153 patients (47.7%) were excluded. Baseline and 3-month cardiac computed tomography scans were reconstructed into 3-dimensional images, and the long and short axes of the PV ostia were quantitatively and qualitatively assessed in a randomized blinded manner by 2 physicians. RESULTS: A total of 299 PVs from 80 patients after either PFA (n = 37) or RFA (n = 43) were enrolled. PV ostial diameters decreased significantly less with PFA than with RFA (% change; long axis: 0.9% ± 8.5% vs -11.9% ± 16.3%; P < .001 and short axis: 3.4% ± 12.7% vs -12.9% ± 18.5%; P < .001). After a combined quantitative/qualitative analysis, mild (30%-49%), moderate (50%-69%), or severe (70%-100%) PV narrowing was observed, respectively, in 9.0% (15 of 166), 1.8% (3 of 166), and 1.2% (2 of 166) of PVs in the RFA cohort but in none of the PVs after PFA (P < .001). Overall, PV narrowing/stenosis was present in 0% and 0% vs 12.0% and 32.5% of PVs and patients who underwent PFA and RFA, respectively. CONCLUSION: This study indicates that unlike after RFA, the incidence and severity of PV narrowing/stenosis after PV isolation is virtually eliminated with PFA.
Keywords: Imaging, Three-Dimensional; počítačová rentgenová tomografie; Nonthermal ablation; Humans; lidé středního věku; Heart Conduction System; venae pulmonales; následné studie; Female; výsledek terapie; převodní systém srdeční; lidé; Atrial Fibrillation; katetrizační ablace; ženské pohlaví; Male; Middle Aged; Tomography, X-Ray Computed; Pulsed field ablation; Pulmonary Veins; Treatment Outcome; Pulmonary vein stenosis; Electroporation; zobrazování trojrozměrné; mužské pohlaví; Catheter Ablation; Atrial fibrillation; Follow-Up Studies; fibrilace síní; Catheter ablation